Mechanical design and performance evaluation of active thermosiphon beam terminal units - Ji, Ke (2021)
The active chilled beam (ACB) system has evolved for more than twenty years, but its limitations in chilled water temperature control, initial cost and condensation stand as the major obstacles for applications especially in tropical regions. Therefore, a novel air-water configuration active thermosiphon beam (ATB) terminal unit, which combines air entrainment effect and thermosiphon effect, is proposed in this study. The mechanical design and working principles of the ATB are introduced. The experimental comparisons of the ATB are conducted under a wide range of operating conditions to estimate its thermodynamic and hydrodynamic performances. Meanwhile, the operating characteristics and efficiency of the terminal unit are evaluated under four sets of criteria: total cooling capacity, entrainment ratio (ER), sensible heat ratio and heat transfer effectiveness. The experimental results show that the cooling capacity of the ATB is around 50% higher than the ACB under nominal conditions. Moreover, the sensible heat ratio (SHR) and heat transfer effectiveness of ATB can reach 42% and 27.3 respectively which validate the feasibility of the proposed terminal unit. The experimental findings provide a guideline for the design and operation of the ATB system.